Sistem Fotoreaktor Elektrolit Biner, Terner, dan Kuarterner Berbasis Elektroda Cu Serabut - ike sabaria; Rahadian Zainul (Departemen Kimia FMIPA UNP, 2020)
Solar cell (photovoltaic cell) is a device that has ability to convert sunlight energy into electrical energy by applying the photovoltaic principle. The photovoltaic principle is defined as a phenomenon of the appearance of an electric voltage due to the contact of two electrodes connected to a solid or liquid system when exposed to solar light. This study aims to determine the maximum power generated from the photoreactor, determine the effect of concentration variations and determine the efficiency of the photoreactor. The method in this study is an experiment using the photovoltaic effect on a photoreactor with CuO / Al electrodes and electrolytes of sodium chloride, sodium hydroxide and aluminum hydroxide. The variables in this study were measurement time and concentration. The variations in the concentration of sodium chloride, sodium hydroxide, and aluminum hydroxide electrolytes used were 0.25 M; 0.5 M; 0.75 M; and 1M. Current and voltage measurements are carried out 3 hours a day for 5 measurement days. The results showed that the optimum concentration was at a concentration of 0.75 M. The maximum power obtained was 0.0184 mWatt in NaCl solution, 0.072 mWatt in Na2SO4 solution and 0.224 mWatt in Al(OH)3 solution, the ability of the electrodes to produce electricity per area of each NaCl 0.00688mWatt / m2, Na2SO4 0.00263 mWatt / m2, Al(OH)3 0.00486 mWatt / m2 with the electrode cross-sectional area used is 0.0183m2. As well as the maximum efficiency of NaCl, Na2SO4, Al(OH)3 obtained is 0.8339%, 0.318% and 0.5890%. From the research results obtained: The greater the concentration of binary, ternary and quaternary solutions, the greater the power produced.